FAKTOR FAKTOR YANG MEMPENGARUHI PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL (Studi Pada SKPD Pemerintah Kabupaten Bengkalis) - Safitri, Devi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The enactment of government regulation number 71 year 2010 about govermentaccounting standards based accrual and also enactment permendagri 64 2013about the application of government accounting standards based accrual on regionalgovernment bring big changes in financial reporting system in Indonesia, namelychange from the base cash toward accrual become the bases full in accrualrecognition goverment financial transactions. This research aims to analyse theinfluence of variable quality of human researces, information system, thecommitment of the organization, and communication to the application of accrualbased government accounting standards. This research conducted in Bengkalisdistrict using data primer namely data from questionnaires filled by respondents.Object used in this research is a work unit (SKPDs) particulary office, the agencyand the departement under the district government Bengkalis. The analytical toolused is multiple linear regression. The result of the research indicated that thevariabel quality of human researces, information system, the commitment of theorganization, and communication of its effect on applying the governmentaccounting standards based accrual.